Performance characteristics of digital current detector in DC-DC converter - Furukawa, Yudai; Maeda, Shusuke; Kurokawa, Fujio; Colak, Ilhami (Intelec, 2015)
The purpose of this paper is to present a performance characteristics of digital current detector in dc-dc converter. The digital peak current mode control dc-dc converter using the voltage-controlled oscillator (VCO) has already proposed. The peak current is detected by using VCO in the proposed method. The gain of amplifier in the current detector affects to the input voltage range of VCO. Also, it affects the transient response. They are discussed by analysing and simulation.